Whole-person health and development: two South Indian initiatives. Issue 5 (4th July 2017) - Long, Katelyn N.G.; Paterson, Gillian; Bhattacharji, Sara
ABSTRACT: In responding to the 2016 reformulation of the United Nation's Sustainable Development Goals, the development community's efforts are focused on a sweep of initiatives aiming to promote whole-society, sustainable development. The ambition of the SDGs is inspiring, but also daunting, and does not always sit easily within national models of economic development. This viewpoint profiles two organisations in the south Indian state of Tamil Nadu, that have decades of experience in whole-person development among scheduled tribes and disability communities. Both organisations serve as timely examples of ongoing holistic, whole-person health and development in the context of new ideals and economic realities.